Buffalo long non-coding RNA gene11007 promotes myoblasts proliferation - Zhang, Ning; Xu, Gaoxiao; Sun, Ping; Wang, Shuzhe; Zhu, Yunchang; Duan, Saixing; Jiang, Mingsheng; Li, Hui; Wei, Xuefeng; Ma, Yun (Frontiers in Veterinary Science, 2022)
Buffalo meat is of good quality because it is lean and tender, and could bring significant cardiovascular benefits. The underlying difference in muscle development and meat quality is a complex and precisely orchestrated process which has been demonstrated to be regulated by long non-coding RNAs (lncRNAs). However, the regulatory role of lncRNAs in the growth and development of buffalo skeletal muscle is still unclear. In this study, the Ribo-Zero RNA-Seq method was used to explore the lncRNA expression profiles of buffalo myoblasts during the proliferation and differentiation phases. A specific set of 9,978 lncRNAs was found. By comparing the expression profiles of lncRNAs, it was found that there were 1,576 differentially expressed lncRNAs (DELs) during buffalo myoblast differentiation. 12 DELs were chosen and subsequently verified in eight different buffalo tissues during fetal and adult stages by using qPCR. Gene11007 was found to be one of the most down-regulated lncRNAs during buffalo myoblasts differentiation and it was subsequently characterized. EdU, CCK-8, qPCR and western blotting assays showed that gene11007 promoted the proliferation of buffalo myoblasts but it had no effect on cell differentiation. Our research may enrich the genome annotations of buffalo and provide a new molecular target for the in-depth understanding of the regulation of lncRNAs in skeletal muscle.